Reviving the death industry. - Ng, Gwendolyn Ser Ling. (2010)
Reviving the Death Industry chronicles Singapore's funeral industry and the changes it is undergoing as a new generation of young, educated, and ambitious Singaporeans takes on the reins. It offers perpectives from old and young, and spots upcoming trends in the death industry as taboos are overcome with an increasingly educated and affluent population who are changing their mindset. Trends like marketing styles embracing new technology, the influx of foreigns in the industry, the popularity of pre-planning and pre-paying for funerals are explored. Finally, it addresses issues of lack of regulation and government support for the small but necessary industry, with authorities and experts alike offering their take on what is to come.